2003
DOI: 10.1152/ajpheart.00086.2003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aging on myocardial metabolic response to dobutamine

Abstract: of aging on myocardial metabolic response to dobutamine. Am J Physiol Heart Circ Physiol 285: H2158-H2164, 2003. First published July 24, 2003 10.1152/ajpheart.00086. 2003.-In humans, under resting conditions there is an agerelated decrease in myocardial fatty acid utilization (MFAU) and oxidation (MFAO) and a relative increase in myocardial glucose utilization (MGU). The impact of age on an individual's myocardial metabolic response to catecholamines is not well defined. Sixteen younger (mean age, 26 Ϯ 5 yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 33 publications
0
21
1
Order By: Relevance
“…This is consistent with previous reports that showed that aged hearts develop increased dependence on glucose and glycogen and yet have reduced ability to upregulate glucose utilization during stresses. [27][28][29] Several differences in energy metabolism observed in the present study likely contribute to the improved tolerance to ischemia-reperfusion injury in old transgenic hearts. First, a greater level of the energy reserve compound PCr is present in old transgenic hearts.…”
Section: Luptak Et Al Cardiac Effects Of Sustained High Glucose Uptakementioning
confidence: 73%
“…This is consistent with previous reports that showed that aged hearts develop increased dependence on glucose and glycogen and yet have reduced ability to upregulate glucose utilization during stresses. [27][28][29] Several differences in energy metabolism observed in the present study likely contribute to the improved tolerance to ischemia-reperfusion injury in old transgenic hearts. First, a greater level of the energy reserve compound PCr is present in old transgenic hearts.…”
Section: Luptak Et Al Cardiac Effects Of Sustained High Glucose Uptakementioning
confidence: 73%
“…Other models of cardiac dysfunction show greater pathology with aging. With aging, hearts shift to greater glucose and less FA use even in the absence of any cardiac pathology (31). Perhaps if a similar process occurs in mice, more PPARγ ligands that are normally oxidized might accumulate in older PPARγ1L hearts.…”
Section: Figurementioning
confidence: 99%
“…Because of its inherent quantitative capabilities and diversity of metabolic radiotracers, PET has played a key role in characterizing perturbations in myocardial carbohydrate use associated with all of these conditions (7)(8)(9)(10)(11). To date, however, measurements of myocardial carbohydrate metabolism in humans have focused solely on glucose use because of the availability of excellent PET tracers of glucose uptake and metabolism such as 18 F-FDG (8,10) and 1-11 Cglucose (7,9,11).…”
mentioning
confidence: 99%